Start-up behaviour of a natural circulation evaporator in brewing industry - Baars, Albert; Delgado, Antonio (BrewingScience - Monatszeitschrift für Brauwissenschaft, 2007)
The start-up behaviour of a wort kettle with a steam heated internal reboiler has been investigated using an open, single tube (length 2.3 m, inner diameter 44.3 mm), steam heated natural circulation evaporator. Hereby, the influence of heating steam pressures (0.18 to 0.45 MPa), hydrostatic head H with water for process medium has been evaluated. This work implies the description of appearing operational modes during start-up, the time for the start-up process and the development of parameter constellations for a gentle heating up of the process medium. On the course to a stationary behaviour with saturated boiling at the outlet of the evaporator, different transient and stationary operational modes can arise e.g. geysering coupled with manometer oscillations followed by a stationary mode, density wave oscillations type I, and a stationary mode with subcooled boiling. Geysering and density wave oscillations feature a strong periodic behaviour. The former mode may lead to serious degradation of wort and apparatus. The transition of modes can be accompanied by a more or less shorttime random behaviour of the circulating mass flow. The course of operational states strongly depends on the parameter settings and the flow pattern in the kettle. Geysering disappears with increasing heating steam pressure and decreasing hydrostatic head. The heating up process is accelerated by rising heating steam pressure and hydrostatic head. In contrast, a more gentle mechanical and thermal treatment of the process medium was obtained with decreasing values for H.
UnivIS-Import:2015-03-09:Pub.2007.tech.ITC.stmmec.startu
Keywords: Evaporator; Internal reboiler; Natural circulation; Operational behaviour; Oscillation; Start-up; Wort kettle